Analysis of Teaching Material Needs for Electronic Student Worksheets for Middle School Science Learning - Fardinelly, Syahria; Slamet, Adeng; Susanti, Rahmi (FKIP - Universitas Riau, 2023)
The development of teaching materials for Electronic Student Worksheets (E-LKPD) is one of the developments of teaching materials in Natural Sciences for Junior High Schools (SMP) which can facilitate students to have high-level thinking abilities, science process skills, as well as the development of interaction. social. This research aims to analyze the need for electronic student worksheets (E-LKPD) in junior high school science learning. Data collection in this research used a questionnaire with qualitative data types to improve students' abilities in using electronic teaching materials with valid, practical and effective live worksheets. The development model used is the Hannafin and Peck development model which consists of needs analysis, development, design and implementation stages, accompanied by Tessmer evaluation. The evaluations used are expert evaluations, one to one, small group and field tests. The characteristic of E-LKPD is that it has an attractive design containing videos, pictures and colors and is multimedia in nature, so it is hoped that it can make students enthusiastic in carrying out learning activities which will have implications for increasing learning outcomes and science process skills.